VD_FINDINFO Jug / 2020 / 120 vom 12. November 2019 - VD Tribunal cantonal (2019)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, RISQUE DE RÉCIDIVE, RISQUE DE FUITE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 231 al. 1 CPP (CH)